Religious Moderation as a Pillar of Tolerance: A Study on the Internalization of Values in Elementary School Students - Rohim, Abdul; Supriadi, Supriadi; Saihan, Saihan (ATTA`DIB, 2025)
This study aims to describe the internalization process of religious moderation values in fostering tolerance among students at SDN 1 Seminyak Badung. The values include national commitment, tolerance, rejection of violence, and respect for local culture. This research employed a qualitative approach with a case study method. Data were collected through in-depth interviews, participant observation, and documentation. Research subjects consisted of the principal, Islamic education teacher, and fifth- and sixth-grade students. The findings reveal that religious moderation values were internalized through teacher role modeling, curriculum and extracurricular integration, an inclusive school culture, and interreligious group-based learning. These strategies successfully cultivated students’ tolerant attitudes, as reflected in respectful social interactions, acceptance of differences, and participation in interreligious and intercultural activities. The results demonstrate that primary schools play a strategic role in shaping students’ moderate character from an early age. This study also fills a gap in research on religious moderation at the elementary education level.